New species of the Microserica lineata group from Laos and Thailand (Coleoptera: Scarabaeidae: Melolonthinae: Sericini) - Bohacz, Claudia; Ahrens, Dirk (Zootaxa, 2020)
Here we describe five further new species of the genus Microserica Brenske, 1894 belonging to the Microserica lineata group: Microserica banvaneue Bohacz & Ahrens, new species, M. ginae Bohacz & Ahrens, new species, M. helferi Bohacz & Ahrens, new species, M. tenasserimensis Bohacz & Ahrens, new species, M. ventrosa Bohacz & Ahrens, new species. The female specimens of Microserica lineata Moser, 1915 are described for the first time. The key to species of the Microserica lineata group is updated and illustrations of genitalia and habitus of adults of the new species are given. Finally, the distribution of the species of the group is mapped.